2017
DOI: 10.1007/s13205-017-0755-0
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic saccharification of pretreated rice straw by cellulases from Aspergillus niger BK01

Abstract: Alkali-assisted acid pretreated rice straw was saccharified using cellulase from Aspergillus niger BK01. The cellulase production by the fungus was enhanced by parametric optimization using solid-state fermentation conditions. Maximum cellulase production (12.0 U/gds of carboxymethyl cellulase, CMCase) was achieved in 96 h, using 6.0% substrate concentration, 7.5% inoculum concentration, 1:2 solid to liquid ratio, at pH 5.5, and temperature 28°C, by supplementation of the fermentation medium with 0.1% carboxym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 52 publications
4
18
1
Order By: Relevance
“…By increasing the pH, the enzyme activity decreased and at pH 7 the enzyme possessed about 40% of its initial activity ( Figure 2). this result is consistent with other researches concerned with the production of cellulases by other Aspergillus species, expressing the optimum activity in acidic condition [17][18][19].…”
Section: Effect Of Ph and Temperature On The Enzyme Activity And Stabsupporting
confidence: 93%
“…By increasing the pH, the enzyme activity decreased and at pH 7 the enzyme possessed about 40% of its initial activity ( Figure 2). this result is consistent with other researches concerned with the production of cellulases by other Aspergillus species, expressing the optimum activity in acidic condition [17][18][19].…”
Section: Effect Of Ph and Temperature On The Enzyme Activity And Stabsupporting
confidence: 93%
“…After enzymatic saccharification, the solid residue and supernatant were separated by centrifugation (4°C for 10 min at 5000 rpm) and subsequently the reducing sugar content in the supernatant was analyzed. The extent of cellulase‐mediated saccharification of delignified AV leaf rind was calculated using Equation (1), (Aggarwal, Goyal, Saini, Yadav, & Gupta, 2017) Saccharification0.25em()%=Reducing sugar obtained×0.90.25emCellulose content in the substrate0.25em×1000.25em …”
Section: Methodsmentioning
confidence: 99%
“…Thus the highest saccharification yield of 69.91 %, corresponding to reducing sugar concentration of 10.58 g/L or 529 mg/g substrate was achieved with alkaline pretreated straw. The reducing sugar concentration of 600 mg/g was achieved with cellulase from Trichoderma harzianium SNRS3 [11] but only 237.8 mg/g reducing sugar was released by crude cellulase from Aspergilus niger BK01 [12]. The results suggested that cellulase from Cellulosimicrobium sp.…”
Section: Effect Of Ph On the Enzymatic Saccharification Of Pretreated Biomassmentioning
confidence: 96%